Defective AMH signaling disrupts GnRH neuron development and function and contributes to hypogonadotropic hypogonadism - Malone, S; Papadakis, G; Messina, A; Mimouni, N; Trova, S; Imbernon, M; Allet, C; Cimino, I; Acierno, J; Cassatella, D; Xu, C; Quinton, R; et al. (eLife Publications, 2019)
Congenital hypogonadotropic hypogonadism (CHH) is a condition characterized by absent puberty and infertility due to gonadotropin releasing hormone (GnRH) deficiency, which is often associated with anosmia (Kallmann syndrome, KS). We identified loss-of-function heterozygous mutations in anti-Müllerian hormone (AMH) and its receptor, AMHR2, in 3% of CHH probands using whole-exome sequencing. We showed that during embryonic development, AMH is expressed in migratory GnRH neurons in both mouse and human fetuses and unconvered a novel function of AMH as a pro-motility factor for GnRH neurons. Pathohistological analysis of Amhr2-deficient mice showed abnormal development of the peripheral olfactory system and defective embryonic migration of the neuroendocrine GnRH cells to the basal forebrain, which results in reduced fertility in adults. Our findings highlight a novel role for AMH in the development and function of GnRH neurons and indicate that AMH signaling insufficiency contributes to the pathogenesis of CHH in humans.